1990
DOI: 10.1016/0166-6851(90)90160-n
|View full text |Cite
|
Sign up to set email alerts
|

Schizodeme analysis of Trypanosoma cruzi stocks from South and Central America by analysis of PCR-amplified minicircle variable region sequences

Abstract: Kinetoplast DNA (kDNA) was isolated from 56 stocks of Trypanosoma cruzi isolated from human patients, animals and insects from Brazil, Venezuela, Colombia and Costa Rica. Comparison of the patterns of digested kDNA on acrylamide gels led to the grouping of several stocks into two schizodemes. Schizodeme analysis was also performed using a set of 330-bp fragments representing all the variable regions of the minicircle DNA molecules, which were obtained by PCR amplification of the kDNA using conserved region pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 13 publications
1
43
0
1
Order By: Relevance
“…The absence of strict correlation between hybridization patterns and sub-clustering contrasted with studies showing that kDNA probes identified distinct monophyletic groups (Brenière et al 1998a) but similar results were observed previously among Bolivian stocks isolated from T. sordida vector (Brenière et al 1998b). The HVRm are highly heterogeneous in sequence (Morel et al 1980, Avila et al 1990) and the mechanisms which generate this diversity are unknown. Additional qualitative and quantitative studies of the different minicircle sequence classes would be necessary to best investigate the diversity and evolution of kDNA minicircles, particularly in Mexico where the vector species participate in sylvatic and domestic cycles.…”
mentioning
confidence: 99%
“…The absence of strict correlation between hybridization patterns and sub-clustering contrasted with studies showing that kDNA probes identified distinct monophyletic groups (Brenière et al 1998a) but similar results were observed previously among Bolivian stocks isolated from T. sordida vector (Brenière et al 1998b). The HVRm are highly heterogeneous in sequence (Morel et al 1980, Avila et al 1990) and the mechanisms which generate this diversity are unknown. Additional qualitative and quantitative studies of the different minicircle sequence classes would be necessary to best investigate the diversity and evolution of kDNA minicircles, particularly in Mexico where the vector species participate in sylvatic and domestic cycles.…”
mentioning
confidence: 99%
“…T. cruzi strains represent subspecies, based on intrinsic characters as antigenic composition (Andrade et al 1981) susceptibility to chemotherapy (Andrade et al 1975, Brener et al 1976), isoenzyme patterns ( Miles et al 1980, Andrade et al 1983, Tibayrenc & Ayala 1988 and genomic profils of kDNA (Morel et al 1980, Avila et al 1990). Studies on the host-parasite relationships have disclosed marked differences in the determinism of tissue lesions, dependent on tropism, virulence and pathogenicity of T. cruzi strains (Andrade et al 1970.…”
mentioning
confidence: 99%
“…Minicircle kDNA integrations behave as mutagens in the host. kDNA has been used for the identification of subgroups of T. cruzi populations (Avila et al 1990). The relationships among distinct parasite populations have been characterized using largely nuclear markers into six discrete typing units (DTUs) (Brisse et al 2000a(Brisse et al ,b, 2001.…”
Section: Interlocking Networkmentioning
confidence: 99%